Explaining the social acceptance of renewables through location-related factors: an application to the Portuguese case - Pinto, Lígia (2021)
The public perception of renewable energy sources is generally positive, due to their role in air pollution and CO2 emission mitigation policies. However, there are local environmental detrimental effects, and empirical evidence is not consistent as to the support of local communities. In the present paper, we analyse the antecedents of public generic perceptions of renewables grounded on objective location-related factors. Personal location-related factors can originate in the involvement of individuals with renewable energy sources. Regional location-related factors concern the importance of the renewable energy source in the district of residence and in relation to other renewables. We implement a questionnaire on public perceptions of renewable energy sources by the general population in mainland Portugal and complement respondent-level responses with renewable energy district information. Regression analysis shows that these objective location-related factors, both personal and regional, help explain public perceptions of renewables and thus we find empirical support for the proposed approach. These results can inform and guide policymakers in tackling future social acceptance issues of renewable energy policies towards lower carbon emissions and less polluting energy production.